Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

sin theta +cos theta =p and secsquare theta +cosec square theta =q then prove that q(p square -1) =2p

sin theta +cos theta =p and secsquare theta +cosec square theta =q then prove that q(p square -1) =2p

Grade:10

1 Answers

Arun
25763 Points
3 years ago

SinA + CosA = p

SecA + CosecA = q

Now, p2 - 1

= (SinA + CosA)2 - 1

= (Sin2A + 2SinACosA + Cos2A) - 1

= [ (Sin2A+Cos2A) + 2SinACosA ] - 1

= [ 1 + 2SinACosA ] - 1

= 2SinACosA [Equation (i)]

So, q(p2 - 1)

= (SecA + CosecA)*(2SinACosA) [from Equation (i)]

= SecA*(2SinACosA) + CosecA*(2SinACosA)

= (1/CosA)*(2SinACosA) + (1/SinA)*(2SinACosA)

= 2SinA + 2CosA

= 2(SinA + CosA)

2p

 

Regards

Arun (askIITians forum expert)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free